Genetically Stable Picornavirus Expression Vectors with Recombinant Internal Ribosomal Entry Sites - Dufresne, Andrew T. (American Society for Microbiology, 2002)
In many respects, picornaviruses are well suited for their proposed use as immunization vectors. However, their inherent genetic instability hinders application for prophylactic purposes. We demonstrate the improved expression and stability of a heterologous insert through a novel vector design strategy that partially replaces noncoding regulatory sequences with coding sequences for foreign gene products.